PENGARUH PENGGUNAAN MEDIA VIDEO PEMBELAJARAN TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIA LSISWA KELAS V SD SE-KECAMATAN GEDANGSARI GUNUNGKIDUL TAHUNAJARAN2015/2016 - Taufik Dwi Kurniawan; Trisharsiwi Trisharsiwi (Universitas Sarjanawiyata Tamansiswa, 2016)
This study aims to determine the tendency of class V student achievement Gedangsari Gunungkidul elementary school districts that use the 2015/2016 school year and the instructional videos that use convetional learning. Reseacrh conducted in school districts Gedangsari with population of 442 and a sample of 120 students. The research used a Quasi Experiment Method. The data collection techniques using techniques documentation and test. Hypothesis testing using t-tes previous test in the form of analysis prerequisite test for normality and homogeneity of variance. The descriptive research result showed that the trend of learning achievement in social science that uses instructional videos included in the category of very high and the use of conventional learning in the high category. T-test result obtained = 5,734, p = 0,000. Because p â‰¤ 0,01 then comparatively there are significant differences of achievement social between using video learning media and the use of conventional media, it can concluded that there was an influence of using learning videos on the IPS learning achievement.